MODELING OF THE INFLUENCE OF THERMIC TREATMENT UPON THE MECHANICAL PROPERTIES OF ALUMINUM-TIN ALLOYS (JOURNAL OF ADVANCES IN PHYSICS, 2015)
In order to master and improve the quality and properties of the final products, the major industrial challenge lies in the possibility of controlling the morphology, size of microstructures that reside within the molded pieces, as well as their defects; this is the fundamental reason according to which we are more and more interested in mastering the growth and germination of such alloys, as well as the developing structures, at the time of solidification process. The modeling reveals as a valuable aid in the mastery of the formation of such heterogeneousness: segregation cells that are incompatible with industrial requirements. The whole work focuses upon the modeling of the segregation phenomenon of the four hypoeutectic alloys, Al1%Sn, Al2%Sn, Al3%Sn and Al4%Sn, as well as the tin effect upon certain mechanical properties of aluminum. Usually, the microstructure and mechanical behavior of such alloys as Al-Sn are directly influenced by some parameters such as composition, cooling velocity and homogenization process.